Pengaruh Konsentrasi Awal Larutan terhadap Penyerapan Ion Logam Berat Cr3+ Menggunakan Biomassa Alga Hijau Mougeotia sp. Yang Diimobilisasi Pada Natrium Silika - Helmi Susanti; Mawardi Anwar (Jurnal Periodic Jurusan Kimia UNP, 2020)
Excessive heavy metal contamination in the environment can have negative effects on the environment and human health, one of which is the metal ion Cr3+. To overcome the increase in heavy metal ions, a biosorption method was used. Efforts made to increase the stability of biomass absorption are immobilization with sodium silica. Immoblization is the process of binding cells into the supporting matrix. The purpose of this study was to determine the optimum conditions for the absorption of Cr3+ metal ions, the initial concentration of the solution and the ratio of absorption to immobilized biomass. The results showed that the optimum absorption of Cr3+ metal ions occurred at the initial concentration of 250 mg/L solution and decreased with increasing concentration. The maximum absorption capacity obtained is 6.7409 mg/g. The biosorption of Cr3+ ions fulfills the Langmuir Isotherm equation with R2 of 0.898.